Hematometra in pubertal girls: A report of two cases and review of literature - Christopher C Amah; Ijeoma C Obianyo; Nene E Agugua-Obianyo; Henry C Nnaji; Obioma A Okezie (International Journal of Medicine and Health Development, 2022)
Haematometra in pubertal girls is a late presentation of congenital genital malformations. A diagnosis of the anomaly is preferably made before menarche. This will avoid the psychosocial trauma and other complications at puberty. We draw attention to the two cases we managed, reviewed the literature, discussed the specific pitfalls in our setting and arouse clinical awareness to the problem. two cases of haematometra in pubertal girls are discussed and the literature is reviewed. The first case is a 12-year-old girl who presented with cyclic lower abdominal pain, abdominal mass and no menarche. Following investigations, a diagnosis of cervicovaginal atresia was made. She eventually had hysterectomy done by request. She is awaiting vaginoplasty. The second patient is a 14-year-old girl who presented with primary amenorrhoea, cyclic lower abdominal cramps and abdominal mass. A diagnosis of imperforate hymen was made. The hymen was excised and the vulva (introitus) re-epithelialized. Both patients have been followed up for 4 years and have been symptom free. Our literature review shows that haematometra presenting in pubertal girls is rare and the causes are commonly congenital. It is either due to malformation of the Mullerian duct system, the urogenital system, or the external genitalia. Associated malformation of the urinary system is significant. Haematometra can pose challenges in management especially in a low resource setting. Early diagnosis and multidisciplinary approach are mandatory to proffer adequate treatment and avert psychological, sexual and reproductive health complications.